Human Resources Management in Multinational Companies: A Central European Perspective - Marzena Stor (Routledge, 2023)
Human resource management (HRM) has a significant impact on companies' performance, as evidenced by research conducted in multinational companies (MNCs) based in Central Europe. This book provides a unique perspective of activities conducted in the HRM field in local subsidiaries of such enterprises. It also presents results verifying many hypotheses for each of the six models for single HRM subfunctions and their four relationships with the results of company performance. Particular chapters are devoted to activities including staffing the organization, shaping employee work engagement and job satisfaction, conducting employee performance appraisal, employee development, managerial staff development, and employer branding. The author used the Partial Least Squares Structural Equation Modeling to verify the research hypotheses. Readers will acquire knowledge about HRM practices in organizations in which the overwhelming ownership capital belongs to MNCs headquartered in Central Europe. The research findings presented confirm the positive impact that HRM activities have on the results of this type of enterprise in such areas as finance, quality, innovation and HRM itself. The research also sheds light on the new, interesting regularities identified in this regard, e.g. the perception of human factor as a competitive factor. This book will be of interest to academics, researchers, and advanced or postgraduate students who are interested in the latest research on HRM in MNCs in the region of Central Europe.
Keywords: 650; company performance; employee development; employee engagement; employee experience; employer branding; HRM; human factor; MNCs; managerial staff development; multinational; performance appraisal; SEM-PLS; staffing